РАЗМЫШЛЕНИЯ О ФИЛОСОФИИ ГЕОМОРФОЛОГИИ - Тимофеев Д.А. (My University, 2003)
The main postulates and conceptions of modern geomorphology are discussed, considering the latter as the science of continuous-discontinuous development of landforms. In the later years the traditional evolution-genetic paradigm is complemented with the growing attention to anthropogenic and ecological geomorphology and to the most general laws of universe and human's place in it.
Keywords: 551.4.01